Parents under siege: the psychological impact of COVID-19 outbreak on children’s caregivers (Swiss Medical Weekly, 2021)
AIMS OF THE STUDY: It is well known that parenting stress is an important but often underestimated psychosocial variable. Data regarding the impact of the corona virus disease 2019 (COVID-19) outbreak on parental psychology are currently lacking. The aim of the present study was to assess parenting stress during the COVID-19 pandemic in Greece.METHODS: An Internet e-survey was conducted adhering to CHERRIES guidelines of the EQUATOR network and released from 16 March to 22 March 2020, using the Perceived Stress Scale (PSS) and Revised Impact of Event Scale (IES-R). A convenience sample of 1105 Greek parents of children with or without chronic or severe underlying disorders was enrolled, identified by a network of collaborating paediatricians across the country, and invited via personal emails.RESULTS: The participation rate was 91.6% and the completion rate was 100%. A total of 178 (16.1%) of the participants had children with underlying disorders (198 affected children in total). Parents of children with underlying disorders had significantly higher stress levels than those of healthy children (PSS 21.22 ± 5.06 vs 19.02 ± 6.85, p